A graphite material and its preparation method and application

During the preparation of graphite negative electrode material, iron tetroxide is deposited and granulated in an intermittent magnetic field, and combined with medium-temperature asphalt as a binder, the problem of high cyclic expansion and graphitization costs of graphite materials is solved, and a higher degree of graphitization and lower expansion rate is achieved.

CN116375017BActive Publication Date: 2025-04-04ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310317068.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-04-04
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have volume expansion problems during circulation, and the graphitization cost is high. How to reduce the energy consumption of cyclic expansion and graphitization has become a problem.

Method used

By depositing iron tetroxide on the surface of the coke powder and mixing granulation in an intermittent magnetic field, combining medium-temperature asphalt as a binder, the graphitization temperature is reduced, the graphitization degree is improved, and the particle OI value is reduced.

Benefits of technology

It effectively reduces the cyclic expansion and preparation cost of graphite materials, improves graphitization and gram capacity, reduces the particle OI value, and improves the disorderly arrangement of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004150476960000081
    Figure BDA0004150476960000081
  • Figure BDA0004150476960000091
    Figure BDA0004150476960000091
  • Figure HDA0004150476980000011
    Figure HDA0004150476980000011
Patent Text Reader

Abstract

The present invention discloses a graphite material and a preparation method and application thereof, belonging to the technical field of lithium ion batteries. The preparation method described in the present invention comprises the following steps: S1. Using an iron source and urea as raw materials, ferroferric oxide is deposited on the surface of coke powder; S2. The solid product obtained in step S1 and medium-temperature asphalt are mixed and granulated in an intermittent magnetic field; S3. The material treated in step S2 is graphitized. The iron source includes a soluble divalent iron salt and a soluble trivalent iron salt. The OI value of the graphite material described in the present invention is between 6 and 9, and the graphite material described in the present invention is applied to negative electrode materials of various lithium ion batteries and electrode materials of capacitors. The preparation method of the present invention can effectively improve the granulation disorder, reduce the particle OI value, reduce cyclic expansion, and effectively reduce the graphitization temperature, save energy and reduce consumption, and reduce costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrodes, and in particular to a graphite material and a preparation method and application thereof. Background Art

[0002] Graphite is the current mainstream negative electrode material, which affects the energy density, fast charging performance, cycle expansion, etc. of the battery. It is the most mature negative electrode material for high energy density industrialization. As a traditional negative electrode material, the process technology of graphite has reached its ceiling, and technological breakthroughs and iterative updates are slow. In order to improve the cycle expansion of graphite negative electrode materials, coke raw materials with higher isotropy are usually selected, and the degree of granulation is increased as much as possible to increase the isotropy of graphite particles, so as to reduce the volume expansion of graphite materials during the cycle. However, the degree of granulation is difficult to control accurately by conventional processes, and how to make the particle arrangement meet people's design expectations has become a problem. On the other hand, in the process of graphite preparation, graphitization has accounted for more than 50% of the cost, and how to reduce energy consumption is another problem facing negative electrode production.

[0003] Therefore, it is necessary to develop a method for preparing graphite materials, improve the granulation disorder, reduce the cyclic expansion of graphite materials, and reduce the graphitization cost. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing a graphite material, which can effectively improve the granulation disorder degree, reduce the particle OI value, and reduce the cyclic expansion and preparation cost of the obtained graphite material.

[0005] According to a first aspect of the present invention, a method for preparing a graphite material is provided, the method comprising the following steps:

[0006] S1. Using iron source and urea as raw materials, ferroferric oxide is deposited on the surface of coke powder;

[0007] S2. The solid product obtained in step S1 and the medium temperature asphalt are mixed and granulated in an intermittent magnetic field;

[0008] S3. The material after step S2 is graphitized;

[0009] The iron source includes soluble ferric iron salts and soluble ferric iron salts.

[0010] The graphite material according to the first aspect of the present invention has at least the following beneficial effects:

[0011] The preparation method of the present invention in-situ grows ferroferric oxide on the surface of coke powder to obtain coke powder coated with ferroferric oxide. During the graphitization process, the ferroferric oxide can be used as a catalyst to promote the graphitization process to be thorough and improve the degree of graphitization. At the same time, the BET value and TD value of the powder are reduced, the gram capacity and the first effect are increased, and the OI value (degree of orientation of graphite grains) of the particles is reduced.

[0012] The traditional graphitization temperature is 2700-3200°C, which consumes a lot of electricity and processing costs. The preparation method of the present invention effectively reduces the temperature of graphitization treatment under the catalytic effect of ferrosoferric oxide, saves energy, reduces consumption, and reduces costs.

[0013] Since ferroferric oxide has magnetic properties, and the present invention artificially intervenes in the granulation process by arranging an intermittent magnetic field, the particles can be effectively prevented from being arranged in an orderly manner during granulation, making the granulation more disordered, and further reducing the OI value to 6 to 9. If the magnetic field is in a constant direction and acts continuously, the orderliness of the arrangement of the coke powder will increase due to the effect of the ferroferric oxide magnetic substance, thereby improving the OI value of the obtained graphite material.

[0014] The preparation method of the present invention has simple and mature processing technology and is feasible for mass production; the raw materials are cheap and easily available and do not require any special additives.

[0015] According to some embodiments of the present invention, the soluble ferrous iron salt includes at least one of ferrous sulfate, ferrous chloride and ferrous nitrate.

[0016] Preferably, the soluble divalent iron salt is ferrous sulfate (FeSO 4 ).

[0017] According to some embodiments of the present invention, the soluble ferric salt comprises at least one of ferric chloride, ferric sulfate and ferric nitrate.

[0018] Preferably, the soluble ferric iron salt is ferric chloride (FeCl 3 ).

[0019] According to some embodiments of the present invention, the molar ratio of the soluble divalent iron salt to the soluble trivalent iron salt is about 2:1.

[0020] According to some embodiments of the present invention, in step S1, the raw material of the coke powder includes at least one of needle coke, petroleum coke and pitch coke.

[0021] According to some embodiments of the present invention, the composition of the petroleum coke is: volatile matter is 2-15%, sulfur content is less than 2%, and ash content is less than 0.5%.

[0022] According to some embodiments of the present invention, in step S1, the Dv50 of the coke powder is 3 to 15 μm.

[0023] Preferably, in step S1, the Dv50 of the coke powder is 6-10 μm.

[0024] According to some embodiments of the present invention, the preparation method further comprises pre-treating the coke powder. The pre-treating is performed when parameters such as particle size of the coke powder are not satisfied.

[0025] The pretreatment includes sequentially mixing, crushing and classifying the raw materials of the coke powder.

[0026] According to some embodiments of the present invention, in step S1, the deposition of ferroferric oxide comprises mixing an aqueous solution of the iron source and an aqueous dispersion of urea and coke powder, and heating the resulting mixture for reaction.

[0027] According to some embodiments of the present invention, the concentration of the aqueous solution of the iron source is 0.2-1 mol / L.

[0028] Preferably, the concentration of the aqueous solution of the iron source is 0.5 mol / L.

[0029] According to some embodiments of the present invention, the urea (CO (NH 2 ) 2 ) concentration is 1~5mol / L.

[0030] Preferably, the urea (CO (NH 2 ) 2 ) concentration is 4 mol / L.

[0031] According to some embodiments of the present invention, in the aqueous dispersion, the mass percentage of the coke powder is 0.1-5%.

[0032] Preferably, in the aqueous dispersion, the mass percentage of the coke powder is 0.3-3%.

[0033] According to some embodiments of the present invention, the heating reaction is carried out under vacuum conditions.

[0034] According to some embodiments of the present invention, the temperature of the heating reaction is 80-110°C.

[0035] Preferably, the temperature of the heating reaction is 95°C.

[0036] According to some embodiments of the present invention, the heating reaction time is 8 to 16 hours.

[0037] Preferably, the heating reaction lasts for 12 hours.

[0038] The heating reaction process is a static reaction, that is, under vacuum conditions, heating to 80-110° C. and standing for 8-16 hours.

[0039] According to some embodiments of the present invention, step S1 further comprises, after depositing the ferrosoferric oxide, performing solid-liquid separation on the obtained mixture, and drying the obtained solid phase component.

[0040] In step S1, in-situ growth of ferroferric oxide (Fe 3 O 4 ), the in-situ growth of ferroferric oxide is carried out in a vacuum reactor, which causes urea to decompose into ammonia and react with divalent iron and trivalent iron to crystallize on the surface of coke powder into magnetic Fe 3 O 4 After solid-liquid separation and drying, the Fe-coated 3 O 4 Coke powder, magnetic Fe 3 O 4 It has the function of catalyzing graphitization and enhancing magnetism.

[0041] According to some embodiments of the present invention, step S2 further comprises premixing the medium temperature asphalt and the solid product obtained in step S1 before mixing and granulating in the intermittent magnetic field.

[0042] According to some embodiments of the present invention, the premixing time is about 1 hour.

[0043] According to some embodiments of the present invention, in step S2, the amount of the medium-temperature asphalt added is 5-20 wt % of all the materials in step S2.

[0044] Preferably, in step S2, the amount of the medium-temperature asphalt added is 15 wt% of all the materials in step S2.

[0045] Medium temperature asphalt is used as a binder to maintain good fluidity and wettability and enhance the strength of bonding. First add the binder according to the proportion, mix evenly, and then heat it up to avoid failure to complete bonding and granulation.

[0046] According to some embodiments of the present invention, the medium-temperature asphalt has a softening point of 70 to 190°C.

[0047] Preferably, the medium-temperature asphalt softening point is 150°C.

[0048] According to some embodiments of the present invention, the asphalt coking value is 20-75%.

[0049] Preferably, the asphalt coking value is 60%.

[0050] According to some embodiments of the present invention, the mixing treatment in step S2 is performed under the condition of: fully mixing by a VC mixer for 40 min to 80 min.

[0051] According to some embodiments of the present invention, in step S2, the magnetic field strength of the intermittent magnetic field is 0.3-1.5T.

[0052] Preferably, in step S2, the magnetic field strength of the intermittent magnetic field is 0.8T.

[0053] According to some embodiments of the present invention, in step S2, the pulse of the intermittent magnetic field is 3 to 10 minutes.

[0054] Preferably, in step S2, the pulse of the intermittent magnetic field is 7 minutes.

[0055] According to some embodiments of the present invention, in step S2, the intermittent magnetic field is an intermittent electromagnetic field.

[0056] The present invention adds an electromagnet to the periphery of the device to generate a magnetic field acting on the inside of the device to establish a directional magnetic field; the electromagnetic field is powered on in an intermittent manner, that is, each time the power is turned on for 3 to 10 minutes, it is stopped for 3 to 10 minutes, and this is repeated.

[0057] According to some embodiments of the present invention, in step S2, the temperature of the mixing and granulating is 25 to 650° C., and the time is 6 to 12 hours.

[0058] Preferably, in step S2, the reaction temperature of the mixing granulation is 25-650° C., and the reaction time is 8 hours.

[0059] In step 2, the mixing and granulation is a heating process, from room temperature to 650° C., and the heating rate is 3° C. / min.

[0060] The purpose of step S2 is to reduce the OI value of the particles and increase the disorder of the particle arrangement.

[0061] According to some embodiments of the present invention, step S2 further includes screening the obtained mixture after the granulation.

[0062] According to some embodiments of the present invention, in step S3, the temperature of the graphitization treatment is 1200-2500°C;

[0063] According to some embodiments of the present invention, in step S3, the atmosphere of the graphitization treatment is an inert atmosphere.

[0064] According to some embodiments of the present invention, in step S3, the inert atmosphere of the graphitization treatment is at least one of nitrogen, helium and argon.

[0065] According to some embodiments of the present invention, in step S3, the duration of the graphitization treatment is 10 to 50 hours, for example, about 15 hours.

[0066] According to some embodiments of the present invention, in step S3, the heating rate of the graphitization treatment is 30-80° C. / h.

[0067] According to some embodiments of the present invention, in step S3, the graphitization treatment equipment is an Acheson graphitization furnace.

[0068] According to some embodiments of the present invention, in step S3, the graphitization treatment includes a first constant temperature treatment and a second constant temperature treatment performed sequentially.

[0069] The temperature of the first constant temperature is 1200-2000°C.

[0070] The first constant temperature duration is 5 to 20 hours.

[0071] The temperature of the second constant temperature is about 2500°C.

[0072] The duration of the second constant temperature is 5 to 10 hours.

[0073] In step S3, the heating rate is controlled during the graphitization treatment process. First, the temperature is kept at 1200-2000° C. for a sufficient time of 5-20 hours. The Fe element obtained by decomposing ferroferric oxide continuously combines with C atoms, and then decomposes and evaporates to form, which prompts the C atoms to form a carbon hexacyclic structure in an orderly manner. The Fe element is discharged with high-temperature gasification; then the graphitization temperature is controlled to rise to 2500° C. and kept for 5-10 hours to improve the graphitization degree of the graphite material.

[0074] According to some embodiments of the present invention, in step S3, the sieving mesh number is 300 meshes. The sieving here has the functions of both preliminary crushing and particle size screening.

[0075] According to a second aspect of the present invention, a graphite material prepared by the above preparation method is provided, wherein the OI value of the graphite material is between 6 and 9, for example, specifically about 8.3.

[0076] According to some embodiments of the present invention, the BET of the graphite material is 1.7 to 1.9 m 2 / g, for example, can be about 1.8m 2 / g.

[0077] According to some embodiments of the present invention, the TD value of the graphite material is 1.02-1.04 g / cc, for example, specifically about 1.03 g / cc.

[0078] According to some embodiments of the present invention, the Dv50 of the graphite material is 11.8-12.0 μm, for example, specifically about 12.0 μm.

[0079] According to some embodiments of the present invention, the graphitization degree of the graphite material is 92.2-94.5%, for example, specifically about 94.5%.

[0080] According to some embodiments of the present invention, the gram capacity of the graphite material is 352-358 mAh / g, for example, can be up to about 358 mAh / g.

[0081] According to some embodiments of the present invention, the first efficiency of the graphite material is 92.1-93.7%, for example, specifically, it can reach 93.7%.

[0082] According to a third aspect of the present invention, a use of the graphite material prepared by the above preparation method in the negative electrode material of a lithium-ion battery and the electrode material of a capacitor is proposed.

[0083] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0084] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0086] Figure 1 This is a graph showing the capacity retention rate results of 3C stage charge / 0.7DC in the cyclic expansion test of the test example of the present invention;

[0087] Figure 2 This is a graph showing the expansion rate results of the 3C stage charge cycle in the cyclic expansion test of the test example of the present invention. DETAILED DESCRIPTION

[0088] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0089] Example 1

[0090] This embodiment provides a graphite material, which is prepared by the following preparation method, which specifically includes the following steps:

[0091] 1) crushing, grinding and classifying needle coke to obtain coke powder with a Dv50 of 6 to 10 μm;

[0092] 2) Prepare FeSO with a total concentration of 0.5 mol / L and a molar ratio of 2:1 4 and FeCl 3 The mixed solution was slowly added to the aqueous dispersion formed by urea and coke powder with a concentration of 4 mol / L, the mass of coke powder being 0.3% of the aqueous dispersion, and stirred thoroughly; the above materials were added to the reactor, the reactor was heated to 95°C and allowed to stand for 12 hours. The obtained product was subjected to solid-liquid separation and the obtained solid product was dried.

[0093] 3) Select medium-temperature asphalt with a softening point of 150°C and a coking value of 60%, and mix it with the solid product obtained in step 2), wherein the addition amount of the medium-temperature asphalt is 15% of the mass of the obtained mixture, and fully mix it in a VC mixer for 1 hour.

[0094] 4) The mixture obtained in step 3) is transferred to a reactor, and an electromagnetic field is introduced into the reactor with a magnetic field strength of 0.8 T. The time interval is controlled at 7 minutes, and intermittent start and stop are maintained. The granulation treatment is carried out for 8 hours at a treatment temperature of 25°C to 650°C and a heating rate of 3°C / min.

[0095] 5) In an inert atmosphere, the granulated product is screened and then graphitized in an Acheson graphitization furnace. Specifically, the graphitization heating rate is 50°C / h, the first constant temperature is 1500°C, the first constant temperature insulation time is 15h, and then the graphitization temperature is controlled to rise to 2500°C and be kept for 10h, and then the graphite material can be obtained by cooling through a 300-mesh sieve.

[0096] Example 2

[0097] This embodiment provides a graphite material, which is prepared by the following preparation method, which specifically includes the following steps:

[0098] 1) crushing, grinding and classifying needle coke to obtain coke powder with a Dv50 of 6 to 10 μm;

[0099] 2) Prepare FeS0 with a concentration of 0.5 mol / L and a molar ratio of 2:1 4 and FeCl 3 The mixed solution was slowly added to the aqueous dispersion formed by urea and coke powder with a concentration of 4 mol / L, the mass percentage of coke powder was 1% of the aqueous dispersion, and the mixture was stirred thoroughly; the above materials were added to the reactor, the reactor was heated to 95°C and allowed to stand for 12 hours. The obtained product was subjected to solid-liquid separation and the obtained solid product was dried.

[0100] 3) Select medium-temperature asphalt with a softening point of 150°C and a coking value of 60%, and mix it with the solid product obtained in step 2), wherein the addition amount of the medium-temperature asphalt is 15% of all materials, and mix them thoroughly for 1 hour in a VC mixer.

[0101] 4) The mixture obtained in step 3) is transferred to a reactor, and an electromagnetic field is introduced into the reactor with a magnetic field strength of 0.8 T. The time interval is controlled at 7 minutes, and intermittent start and stop are maintained. Granulation treatment is carried out for 8 hours at a treatment temperature of 25°C to 650°C.

[0102] 5) In an inert atmosphere, the granulated product is screened and then graphitized in an Acheson graphitization furnace. Specifically, the graphitization heating rate is 50°C / h, the first constant temperature is 1500°C, the first constant temperature insulation time is 15h, and then the graphitization temperature is controlled to rise to 2500°C and be kept for 10h, and then cooled to pass through a 300-mesh sieve to obtain a graphite material.

[0103] Example 3

[0104] This embodiment provides a graphite material, which is prepared by the following preparation method, which specifically includes the following steps:

[0105] 1) crushing, grinding and classifying needle coke to obtain coke powder with a Dv50 of 6 to 10 μm;

[0106] 2) Prepare FeS0 with a concentration of 0.5 mol / L and a molar ratio of 2:1 4 and FeCl 3 The mixed solution was slowly added to the aqueous dispersion formed by urea and coke powder with a concentration of 4 mol / L, the mass percentage of coke powder was 3% of the aqueous dispersion, and the mixture was fully stirred; the above materials were added to the reactor, the reactor was heated to 95°C and allowed to stand for 12 hours. The obtained product was subjected to solid-liquid separation and the obtained solid product was dried.

[0107] 3) Select medium-temperature asphalt with a softening point of 150°C and a coking value of 60%, and mix it with the solid product obtained in step 2), wherein the amount of medium-temperature asphalt added is 15% of the mixture obtained in this step, and mix thoroughly for 1 hour in a VC mixer.

[0108] 4) The mixture obtained in step 3) is transferred to the reactant, and an electromagnetic field is introduced into the reactor with a magnetic field strength of 0.8 T. The time interval is controlled at 7 minutes, and intermittent start and stop are maintained. The granulation treatment is carried out for 8 hours at a treatment temperature of 25°C to 650°C.

[0109] 5) In an inert atmosphere, the granulated product is screened and then graphitized in an Acheson graphitization furnace. Specifically, the graphitization heating rate is 50°C / h, the first constant temperature is 1500°C, the first constant temperature insulation time is 15h, and then the graphitization temperature is controlled to rise to 2500°C and be kept for 10h, and then the graphite material can be obtained by cooling through a 300-mesh sieve.

[0110] Comparative Example 1

[0111] This comparative example provides a graphite material, which is different from Example 1 in that:

[0112] Step 2) is not included, that is, ferrosoferric oxide is not deposited on the surface of the coke powder.

[0113] Comparative Example 2

[0114] This comparative example provides a graphite raw material, which is different from Example 1 in that:

[0115] (1) does not include step 2);

[0116] (2) The graphitization conditions in step 5) are 3000°C and 20h.

[0117] Comparative Example 3

[0118] This comparative example provides a graphite material, and the specific preparation method is different from that of Example 1 in that:

[0119] (1) does not include step 2)

[0120] (2) Between step 4) and step 5), ferrosoferric oxide particles are added to the product obtained in step 4), and the ratio of the added ferrosoferric oxide to the product obtained in step 4) is the same as the deposition ratio in step 2) of Example 1.

[0121] Comparative Example 4

[0122] This comparative example provides a graphite material, and the specific preparation method is different from that of Example 1 in that:

[0123] In step 4), the magnetic field is a constant magnetic field rather than an intermittent magnetic field.

[0124] Comparative Example 5

[0125] This comparative example provides a graphite material, and the specific preparation method is different from that of Example 1 in that:

[0126] In step 4), no magnetic field is introduced.

[0127] Test Case

[0128] Preparation of lithium-ion soft pack batteries:

[0129] 1. Positive electrode preparation: Lithium cobalt oxide (Xiamen Tungsten New Energy, L906) with a charging cut-off voltage greater than 4.48V, conductive carbon, and adhesive (polyvinylidene fluoride) are mixed evenly in N-methylpyrrolidone solvent at a mass ratio of 97.6:1.1:1.3 to form a positive electrode slurry, which is then coated on aluminum foil and dried, and then cold pressed and slit to form positive electrode sheets.

[0130] 2. Negative electrode preparation: The graphite materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 were mixed evenly with carboxymethyl cellulose (CMC) and SBR in a mass ratio of 97.7:1.1:1.2 in deionized water to form a negative electrode slurry, which was then coated on a copper foil and dried, and then cold pressed and slit to form a negative electrode sheet.

[0131] 3. Cell production: The above-mentioned positive electrode sheet, conventional separator, and negative electrode sheet are wound into a cell, the positive electrode is spot-welded with an aluminum tab, and the negative electrode is spot-welded with a nickel tab; then the cell is placed in an aluminum-plastic packaging bag, and a high-voltage electrolyte is injected, N / P=1.05, the design capacity is 5Ah, and the liquid retention coefficient is 1.55. After packaging, formation, and capacity division processes, a soft-pack lithium-ion battery is made.

[0132] Button lithium ion half-cell production:

[0133] The graphite materials of Examples 1 to 3 and Comparative Examples 1 to 2 were used as electrode materials, lithium sheets were used as counter electrodes, and were assembled into button-type lithium-ion half-cells together with a diaphragm and an electrolyte in a glove box filled with argon gas to test the gram capacity.

[0134] The test conditions of gram capacity are: 0.05C discharge to 5mV, then 0.05mA discharge to 5mV, 0.02mA discharge to 5mV, 0.1C charge to 2.0V. Record the discharge gram capacity and charge gram capacity of the button battery, and calculate the first efficiency, which is the ratio of charge gram capacity to discharge gram capacity. The test results are shown in Table 1.

[0135] Cyclic expansion test of battery cells:

[0136] Cycle conditions: soft pack lithium ion battery was tested, cycled at 25℃, charging mode: 3.0C CC (constant current charging) to 4.2V, constant voltage to 1.8C, 1.8C constant current to 4.3V, constant voltage to 1.5C, 1.5C constant current to 4.48V, constant voltage to 0.05C, and then 0.7C DC discharge to 3.0V. Test results are as follows Figures 1-2 shown.

[0137] This test example also tests the physical and chemical properties of the graphite materials obtained in the embodiments and comparative examples, and tests the specific surface area (BET), tap density (TD), particle size and OI value.

[0138] BET: Reference standard (Measurement criteria): GB / T 19587-2017;

[0139] TD: Reference standard (Measurement criteria): GB / T 5162-2006;

[0140] XRD: Reference standard (Measurement criteria): GB / T 24533-2019.

[0141] Table 1 Test results of physical and chemical properties of graphite materials prepared in Examples and Comparative Examples

[0142]

[0143]

[0144] According to the results in Table 1, in Examples 1 to 3, as the liquid-to-solid ratio of coke powder and urea increases, the BET and Dv50 values ​​are not much different, but the OI value decreases sharply first and then stabilizes, which indicates that the magnetic coating layer grows from less to more, and the disorder of the particle arrangement increases; the change in gram capacity gradually increases, which indicates that the magnetic Fe 3 O 4 The higher the content, the more significant the catalytic graphitization effect, but it tends to be stable after exceeding a certain value.

[0145] In Comparative Example 1, no mixed solution of ferrous sulfate and ferric chloride and urea were added, and no in-situ magnetic coating was performed. Under the same graphitization conditions, graphitization was not thorough, resulting in a large BET of the powder, a minimum TD, a low gram capacity and first efficiency, and a large OI value. In Comparative Example 2, the graphitization temperature was increased, and the physical and chemical data were slightly different from those of the examples, but the OI value was larger than that of Examples 1 to 3 using in-situ magnetic coating. In Comparative Example 3, an equal amount of magnetic Fe was directly added. 3 O 4 After (no in-situ growth), the physical and chemical data are not much different, but the OI value is large, which has no effect on directional granulation. After the constant magnetic field is used in Comparative Example 4, the arrangement direction of the raw coke is disturbed and can only be along the direction of the magnetic field, and the granulation disorder cannot be achieved, so the OI value is the largest, and other physical and chemical data are equivalent; Comparative Example 5 does not add a magnetic field, and the conventional granulation process, the OI value does not decrease, and other physical and chemical parameters are equivalent.

[0146] Combination Figure 1 and Figure 2 The expansion data show that the present invention uses in-situ magnetic coating and intermittent granulation under a magnetic field, which increases the disorder of secondary particles and reduces the OI value of the material, which can significantly reduce the cycle expansion from the original 12% to about 8% after 1200 cycles. The cycle performance is significantly improved, and the capacity retention rate can exceed 85% after 1200 cycles.

[0147] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a graphite material, characterized in that: The preparation method comprises the following steps: S1. Using iron source and urea as raw materials, ferroferric oxide is deposited on the surface of coke powder; S2. The solid product obtained in step S1 and the medium temperature asphalt are mixed and granulated in an intermittent magnetic field; S3. The material after step S2 is graphitized; The iron source includes soluble ferric iron salts and soluble ferric iron salts.

2. The preparation method according to claim 1, characterized in that: In step S1, the raw material of the coke powder includes at least one of needle coke, petroleum coke and pitch coke.

3. The preparation method according to claim 1, characterized in that: In step S1, the deposition of ferrosoferric oxide comprises mixing an aqueous solution of the iron source and an aqueous dispersion of urea and coke powder, and heating the obtained mixture for reaction.

4. The preparation method according to claim 3, characterized in that: In the aqueous dispersion, the mass percentage of the coke powder is 0.1-5%.

5. The preparation method according to claim 3, characterized in that: The concentration of urea in the aqueous dispersion is 1-5 mol / L.

6. The preparation method according to claim 3, characterized in that: In the aqueous solution, the concentration of the iron source is 0.2-1 mol / L.

7. The preparation method according to claim 3, characterized in that: The heating reaction is carried out under vacuum conditions.

8. The preparation method according to claim 3, characterized in that: The temperature of the heating reaction is 80-110° C., and the duration of the heating reaction is 8-16 hours.

9. The preparation method according to claim 1, characterized in that: In step S2, the amount of the medium-temperature asphalt added is 5-20wt% of all the materials in step S2.

10. The preparation method according to claim 1, characterized in that: In step S2, the magnetic field strength of the intermittent magnetic field is 0.3-1.5T.

11. The preparation method according to claim 1, characterized in that: In step S2, the pulse time of the intermittent magnetic field is 3 to 10 minutes.

12. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the mixing and granulation is 25-650° C., and the time is 6-12 hours.

13. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the graphitization treatment is 1200-2500°C.

14. The preparation method according to claim 1, characterized in that: In step S3, the graphitization treatment is carried out in an inert atmosphere.

15. The preparation method according to claim 1, characterized in that: In step S3, the graphitization treatment is performed for 10 to 50 hours.

16. The preparation method according to claim 1, characterized in that: In step S3, the heating rate of the graphitization treatment is 30-80°C / h.

17. A graphite material obtained by the preparation method according to any one of claims 1 to 16, characterized in that: The OI value of the graphite material is between 6 and 9.

18. Use of the graphite material obtained by the preparation method according to any one of claims 1 to 16 in negative electrode materials for lithium-ion batteries and electrode materials for capacitors.

Citation Information

Patent Citations

  • Preparation method of high-capacity and low-resilience graphite anode material for lithium-ion battery

    CN105390673A

  • Artificial composite graphite negative electrode material, lithium ion battery, preparation method and application

    CN111244453A